Retraining not redundancy : innovative approaches to industrial restructuring in Germany and France - Bosch, Gerhard (Geneva : International Institute for Labour Studies, 1990)
This book, which was originally published in German tells us, first of all, how the retrenchment of employment was accomplished in the Federal Republic of Germany and France. Although there are many important differences, we do find a number of similarities in this regard in the two countries. The author's investigation of the measures implemented in the Federal Republic of Germany and France is based on 14 case studies. He describes in detail the problems raised by the new approaches to labour market policy and assesses their chances of success. In conclusion, the author argues for an extension of active labour market policies in the event of company and regional restructuring.
Includes bibliographical references (p. [175]-183).
rpm 30/08/16
Loans
Keywords: Occupational retraining; Occupational retraining; Full employment policies -- Germany; Full employment policies -- France; Vocational qualifications -- Germany; Vocational qualifications -- France